Evolution of Interfacial Structure and Stress Induced by Interfacial Lattice Mismatch in Layered Metallic Nanocomposites. Issue 8 (26th June 2018) - Hao, Huali; Lau, Denvid
Abstract: The interfacial structure directly affects the intrinsic residual stress caused by the interfacial lattice mismatch in layered metallic composites. This stress plays a dominant role in the mechanical, optical, magnetic, and thermal properties of nanocomposites. Here, the interfacial structure evolution and atomistic origin of intrinsic residual stress are figured out through the in situ characterization of atom arrangement and rearrangement in layered metallic nanocomposites with different interfacial misfit by using an atomistic approach. It is found that with the increment of the interfacial misfit, the interface roughens while the intrinsic residual stress increases and then reduces. The film structure dominates the evolution of interfacial structure and intrinsic residual stress when the interfacial misfit is low, whereas the effect of substrate structure on the interface and the stress is as important as the film structure with the increase of the interfacial misfit. The work demonstrates how the film structures affect the interfacial structure and intrinsic stress in layered metallic nanocomposites. Both the film and substrate structures should be taken into consideration to design layered composites with excellent properties. Abstract : The effect of interfacial lattice mismatch on the interfacial structure evolution is investigated. The interfacial roughness increases with the interfacial misfit resulting from atom rearrangements caused by stress relaxation. The rough interface is attributed to the film deformation when the interfacial misfit is small, whereas the substrate deformation also contributes to the interfacial roughness when this misfit is too large.